Least cost path analysis for alternative road network assessment of landslide-prone NH-2, Mizoram, NE India - Jonmenjoy Barman; Brototi Biswas; Jayanta Das; Fahdah Falah Ben Hasher; Mohamed Zhran (Geocarto International)
Mizoram, one of the hilly states in northeast India, is prone to frequent landslides. Such regular calamities prove to be catastrophic to the road networks of the region. The (National Highway- 2) NH-2, the main road in Mizoram connecting the northern side of Mizoram with the southern part of the state, is particularly susceptible to landslides. This study aims to propose an alternative route, less vulnerable to landslides, as an alternative to NH-2. To achieve this, the Analytical Hierarchy Process (AHP), was applied to determine the importance of factors. The least-cost path analysis using the cost raster, revealed an alternative route from the desired location towards the east, deviating from the current path. As a result, we found that the existing road design, which neglected environmental considerations, could lead to route selection through restricted zones, potentially causing environmental damage through recurring landslides and increasing financial expenses.